Experiences with Web Search on Medical Concerns and Self Diagnosis - White, Ryen W.; Horvitz, Eric (AMIA Annual Symposium Proceedings 2009, 2009)
The wealth of medical information on the Web makes it convenient for non-experts to conduct their own diagnosis and healthcare assessment based on limited knowledge of signs, symptoms, and disorders. We present the findings of a survey aimed at exploring laypeoples' activities and experiences with using Web search to pursue explanations for symptoms. Survey findings suggest that the Web may influence anxiety levels and behaviors of those searching for information on undiagnosed conditions. A better understanding of consumer experience regarding the use of the Web to interpret symptoms can assist in the refinement of healthcare content and retrieval